Human Organ Culture: Updating the Approach to Bridge the Gap from In Vitro to In Vivo in Inflammation, Cancer, and Stem Cell Biology - Al-Lamki, Rafia S.; Bradley, John R.; Pober, Jordan S. (Frontiers in Medicine, 2017)
Human studies, critical for developing new diagnostics and therapeutics, are limited by ethical and logistical issues and preclinical animal studies are often poor predictors of human responses. Standard human cell cultures can address some of these concerns but the absence of the normal tissue microenvironment can alter cellular responses. Three-dimensional (3D) cultures that position cells on synthetic matrices, or organoid or organ-on-a-chip cultures, in which different cell spontaneously organize contacts with other cells and natural matrix only partly overcome this limitation. Here we review how human organ cultures (HOCs) can more faithfully preserve in vivo tissue architecture and can better represent disease-associated changes. We will specifically describe how HOCs can be combined with both traditional and more modern morphological techniques to reveal how anatomic location can alter cellular responses at a molecular level and permit comparisons among different cells and different cell types within the same tissue. Examples are provided involving use of HOCs to study inflammation, cancer and stem cell biology.